1988
DOI: 10.1111/j.1600-0447.1988.tb05168.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal outcome in drug addiction

Abstract: A sample of 524 young drug addicts consecutively treated at a special hospital ward has been followed by registers for an average of 10 years. A total of 62 were found to have died drug-related deaths at an average age of 28 years; 19 of them had committed suicide. Representativeness of the sample is investigated. Sex and choice of drugs were predictive factors behind fatal outcome: male opiate addicts died 5.4 times and male amphetamine abusers 2.5 times as often as expected. The males were exposed to greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1
5

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 24 publications
4
54
1
5
Order By: Relevance
“…Suicide attempters also reported more psychological distress, use of benzodiazepines, time in treatment and less criminality. This is in line with other studies of suicide risk among substance-abusing people [9,11,12,23,24].…”
Section: Discussionsupporting
confidence: 80%
“…Suicide attempters also reported more psychological distress, use of benzodiazepines, time in treatment and less criminality. This is in line with other studies of suicide risk among substance-abusing people [9,11,12,23,24].…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies from various continents have shown that males are generally overrepresented in FOD cases [8,11,14,15,16,17,18,19]. Most recent research confirms this finding [20,21,22,23].…”
Section: Introductionsupporting
confidence: 74%
“…Beregnet overdødelighet blant stoffmisbrukere er i størrelsesorden fra 5 til 30 (altså 5 til 30 ganger høyere dødelighet enn i befolkningen ellers) (31)(32)(33). Norske studier av stoffmisbrukere viser at dødeligheten ligger på ca.…”
Section: Dødelighet Og Forhøyet Dødelighet Blant Stoffmisbrukereunclassified
“…Mannlige stoffmisbrukere synes å ha en noe høyere dødelighet enn kvinnelige, mens i befolkningen generelt finner vi at dødeligheten er dobbelt så høy blant unge menn (25-44 år) som blant unge kvinner. Derved blir overdødeligheten blant kvinnelige stoffmisbrukere høyere enn blant mannlige stoffmisbrukere (31)(32)(33).…”
Section: Dødelighet Og Forhøyet Dødelighet Blant Stoffmisbrukereunclassified